Evaluation of miR-122 levels in chronic HBV and liver cirrhosis patients - Ebrahimifard, Mohammad; Zandi, Mahshid; Moradi, Abdolvahab (Archives of Medical Laboratory Sciences, 2019)
Background: MicroRNA is a type of small RNA of about 22 nucleotide length. Most popular miRNAs are found in the liver and are extensively important in determining the biological and clinical functions. MicroRNA, in host cells, may impact the replication of viruses either positively or negatively. In this study the miR-122 expression was examined and compared in three groups, two sample groups of patients with chronic hepatitis and hepatitis B virus-associated cirrhosis, and a healthy control group. Materials and Methods: In this study, 108 samples of whole blood were taken from each participant. Then the miRNA expression evaluation was conducted through relative real time PCR. Results: The results indicated that miR-122 expression was elevated in patients with chronic hepatitis B and HBV related cirrhosis about 1.8 times (P<0.05) more than control group which is statistically significant. Conclusion: According to the results of this study, measuring the miR-122 expression levels may be used as a biomarker and an indicator of the disease progression of chronic hepatitis B to HBV related cirrhosis to HCC, but needs more investigations and more samples.